Aplikasi Media Pembelajaran Pendidikan Agama Islam Mengggunakan Card Sord - Riyadi Tamrin, Ahmad; Hastuty, Ade (Jurnal Sintaks Logika, 2024)
Islamic religious education is an important aspect of forming students' character and morals, including at the early childhood education level. In the current digital era, the use of technology can be an effective means of learning Islamic religious education that is interactive and attracts attention. The aim of this research is to create a card sort application to introduce hijaiyah letters to young children. This research method uses quantitative research using the PHP programming language. The research was conducted for three months at the Pilot State Early Childhood Education School, Sidenreng Rappang Regency. The results of the research show that the learning process using card sort can introduce material about recognizing hijaiyah letters and punctuation and how to pronounce letters correctly in video form, making it easier for children to understand letter material.